Bait selection study of the invasive European green crab (Carcinus maenas) in Newfoundland, Canada - Butt, Mary Alliston, 1993- (2017)
The European green crab (Carcinus maenas) is an ecosystem engineer, due to their advanced resiliency to environmental factors. They can tolerate a wide range of salinity and temperature, and have great dispersal capabilities. As true opportunistic scavengers and with low preference to a specific habitat, green crabs have become the ultimate marine invasive species. Newfoundland and Labrador, Canada, is one of many locations affected by this invasive species. They are affecting eel grass (Zostera marina) beds, competing with native rock crab (Cancer irroratus), foraging on juvenile American lobsters (Homarus americanus). This research is focused on the bait used in eradication efforts of green crabs, testing the commonly used Atlantic herring (Clupea harengus), Atlantic cod (Gadus morhua), short-fin squid (Illex illecebrosus), and blue mussels (Mytilus edulis). Though all baits caught green crabs of similar carapace width and sex, Atlantic cod was resulted with a significant higher catch per unit effort than the other bait species tested in this study. Evrópski Grænkrabbinn (Carcinus maenas) er líffræðilega ótrúlegur. Hann hefur háþróað þol og seiglu sem ekki þekkist í öðrum krabbadýrum. Þeir þola miklar breytingar á hita- og seltustigum í sjónum og mikla getu til að fjölga sér. Eins og sönn tækifærissinnuð dýr sem eru sveigjanleg þegar kemur að vali á búsvæði, hafa Grænkrabbar orðið hinar fullkomnu ágengu lífverur. Nýfundnaland og Labrador, Canada, eru tvö af mörgum svæðum sem orðið hafa fyrir barðinu á þessum ágengu lífverum, þar sem þær hafa áhrif á Álinn sjávargróður (Zostera marina), og keppast við innfæddu Steinkrabbana (Cancer irroratus) um ungan Amerískan humar (Homarus americanus) sem æti. Þessi rannsókn er um þau mismunandi áhrif beitunnar sem notuð er í tilraun til að útrýma Grænkrabbanum, þ.e. Atlantshafs Síld (Clupea harengus), Atlantshafs Þorsk (Gadus morhua), Smokkfisk (Illex illecebrosus), og Kræklingi (Bláskel) (Mytilus edulis). Þrátt fyrir að allar beiturnar hafi veitt krabba í svipuðum ...